Legal Issues for Ensuring Security in Tourism and Countering Terrorist Threats - KOLESNIKOV, Yuriy A.; PUSHKAR, Maryna V.; VISHNEVSKA, Yulia V.; SHVETS, Yuriy Yu. (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018DO - 10.14505//jemt.9.4(28).13, 2018)
The development of terrorism is increasingly contributing to the debate about its impact on the tourism sector. Thus, this article is aimed to explore the place of terrorism in the international legal regulation of tourism. The study was carried out by integrated approach to legal expertise of documents of international organizations. Based on the fact that attacks on foreign tourists have increased in certain regions of the world, relation between tourism and terrorism was established. It was revealed that The Hague Declaration on Tourism is the main international legal and regulatory act in the field of tourism. We came to conclusion that complexity of regulation of international tourism is that tourism actually affects on all branches of law. To solve this problem, it is necessary to develop a new declaration, focused on principles of countering terrorist threat to international tourism and tourists.